Hurricane Impacts on Florida’s Agriculture and Natural Resources: AE528/AW528, 10/2018 - Her, Young Gu; Smyth, Ashley; Fletcher, Palela; Bassil, Elias; Stingl, Ulrich; Brym, Zachary; Qui, Jianxiao (EDIS, 2018)
Hurricanes are the most powerful and largest weather event happening in the air, affecting almost everything in their paths. Their strong winds and heavy rain can directly impact both inland and coastal areas in short periods, usually around a day. Understanding hurricane effects is the first step to preparing for hurricanes. The effects of hurricanes can be comprehensive and long-lasting, even permanent, at the spatial scales of a single molecule to whole ecosystems. Much effort has been made to come up with ways to accurately predict, effectively prepare for, and quickly recover from hurricanes, but their sizes and complexity make this difficult. Multidisciplinary collaborations are required to improve our understanding of hurricanes. Here, we review basic facts of hurricanes and their effects in Florida and speculate on how they might affect Florida’s agriculture and natural resources. Examples and speculations provided in this article demonstrate how weather, agriculture, environment, and ecosystem are connected to each other across spatial scales ranging from microorganisms to an entire landscape.